The Effectiveness of using Symbolic Modeling Technique through Empathy Training to overcome Bullying Behavior of Students in Raudhatul Athfal - Ahyia, Yunita Mardianti; Pandang, Abdullah; Saman, Abdul (IKIP Siliwangi, 2024)
English: This study aims to reduce bullying behavior in early childhood through empathy training-based interventions using symbolic modeling techniques. The subject of the study is a 5-year-old boy with the initials RA from RA Al-Muslim Kota Baubau. The method used is an experiment with a single-subject design (Single Subject Research, SSR) and an A-B-A design. Data was collected through observation using a behavior monitoring instrument that recorded the frequency of RA's bullying behavior during the intervention. Visual analysis was conducted to compare the observation results in three conditions: Baseline A1 (before the intervention), Baseline B (during the intervention), and Baseline A2 (after the intervention). The results showed a significant decrease in bullying frequency from a very high category in Baseline A1 (average 14.6) to medium in Baseline B (average 6.2), and low in Baseline A2 (average 2.2). The intervention used short animated films teaching empathy, proving to be effective. Schools can integrate empathy training programs as a preventive and rehabilitative effort against bullying. Indonesia: Penelitian ini bertujuan mengurangi perilaku bullying pada anak usia dini melalui intervensi berbasis latihan empati dengan teknik modeling simbolik. Subjek penelitian adalah anak laki-laki berusia 5 tahun berinisial RA dari RA Al-Muslim Kota Baubau. Metode yang digunakan adalah eksperimen dengan desain subyek tunggal (Single Subject Research, SSR) dan desain A-B-A. Data dikumpulkan melalui observasi dengan instrumen monitor perilaku yang mencatat frekuensi bullying RA selama intervensi. Analisis visual dilakukan untuk membandingkan hasil observasi dalam tiga kondisi: Baseline A1 (sebelum intervensi), Baseline B (selama intervensi), dan Baseline A2 (setelah intervensi). Hasil menunjukkan penurunan signifikan dalam frekuensi bullying dari kategori sangat tinggi pada Baseline A1 (rata-rata 14,6) menjadi sedang pada Baseline B (rata-rata 6,2), dan rendah pada Baseline A2 (rata-rata 2,2). Intervensi menggunakan film animasi pendek yang mengajarkan empati terbukti efektif. Sekolah dapat mengintegrasikan program latihan empati sebagai upaya preventif dan rehabilitatif terhadap bullying.